Low Cost ND: YAG Medical Laser as a Lithotripter and Laser Cautery Machine (Global Journal of Medical Research, 2020)
Introduction-Lasers have extensive application in medical sciences today but unfortunately the cost of medical Lasers is exorbitant and it is beyond the capacity of an average doctor to afford it. To solve this problem, I did my own research and developed low cost medical Laser which most of the doctors can afford.